On Torture - Bingyu, Liu (2013)
The torture issue can be regarded as one of the most important issue in the human rights protection sphere. This paper returns to the intriguing moral and legal foundations of both sides to lay out what motivates it and what main arguments and concerns exist, to let any conclusion made on unbiased grounds. Though the analysis, we can briefly conclude that: on the one side, torture is a palpable evil and must be morally and legally taboo in almost all circumstances. On the other side, due to the lack of definite perception of what can be called extreme situations, and considering the defects of torture warrants, whether torture can be justified under certain circumstances is still debatable. What this paper is trying to figure out are the differences between theories, and to find out the defects and values of each theory. The balance of uncertain and intriguing interests and values on torture bring the room for debatin